Fantasy, Love and Representation of Body in Dante Gabriel Rossetti’s “The Blessed Damozel” and “Jenny” - Sharma, Prachi; Antony, Naina Jai; LA, Liba (Journal of Advanced Research in English & Education; Vol 5 No 3 (2020): Journal of Advanced Research in English & Education, 2020)
The Victorian Era is an era eponymous to the reign of Queen Victoria who ascended the English throne in 1837. The Victorian Era was a period of rapid changes from scientific advancements, industrial revolution, religious sentiments, literary and cultural output and political establishments. This period stood witness to the political and religious mayhem pertaining to stringent Victorian moral beliefs that showed social hypocrisy about sexuality and domestic propriety. This Victorian prudishness was encountered by a spirit of enlightenment induced by the works of Victorian poets and writers like Tennyson, Robert Browning, D.G. Rossetti, John Ruskin and Mathew Arnold. Art and Literature served a moral purpose in developing a morally uplifted society, conscious of a growing individuality. The Pre-Raphaelite Brotherhood induced aesthetic pleasure to celebrate art and the artists to create a medium of artistic exuberance. D.G. Rossetti, along with William Morris, John Everett William Holman Hunt established the Pre-Raphaelite Brotherhood in September 1848. It was a movement pioneered to embrace the idea that poetry and painting are sister arts. The Movement is synonymous tothe medieval and early Renaissance art and helping to revolutionize contemporary art. Jules Paul Seigel states that “Rossetti’s poetry illustrates an artistic base than mere fine description and verse painting which is freer from the trick of ‘word-painting’”(683). His works had an impression of the medieval revivalist trend that explained the earlier painters were “Nearer to fact” and less “Artificial”. His poetry and paintings are a manifestation of the Italian love poetry where the concept of love transcends spiritual boundaries and portrays women either as separated lovers or as sexual objects. His poetry has a Dantesque quality of “Romance of Losses” depicted through mythical charcters DG. Rossetti’s two poems “Blessed Damozel” and “Jenny” exemplify the individual depictions of ecstasy, reverie, love, reunion and death in a subtle manner.